In vitro pollen germination and staining methods for pollen viability assessment in sunflower (Helianthus annuus L.): IN VITRO POLLEN GERMINATION AND STAINING METHODS IN SUNFLOWER - VANI KAMMAR; I SHANKER GOUD; VIKAS V. KULKARNI; R LOKESHA; S N VASUDEVAN (Journal of Oilseeds Research, 2013)
Pollen viability in 207 sunflower (Helianthus annuus L.) genotypes were assessed using staining technique and germination method. Pollen viability by staining technique varied from90.42 to 98.99 % and by germination method it ranged from 27.06 to 79.59 %. Six genotypes viz., GP-808, GP-6-794, GP-6-854, GP-6-906, GP-6-1477 and GP-6-83 recorded higher germination per cent ranging from 75 to 79 and pollen tube length ranging from 42.12 to 149.10 µm, indicating that both pollen germination and staining methods can be employed to assess the viability in sunflower to identify highly competitive pollen genotypes.